ENTREPRENUERSHIP DALAM PEMBERDAYAAN DIRI MASYARAKAT MISKIN - Siti Rohima (Department of Development Economics, Universitas Sriwijaya, 2015)
Poverty is a very complex and multidimensional. Many programs that have been done to tackle poverty, but the results are not optimal. Thus, it takes the efforts of poor people to explore the potential of self through self-empowerment by enhancing the entrepreneurial spirit.The research location in the District of Alang-Alang Lebar. This study used a qualitative approach with symbolic interasionik method. Methods of data collection using observation, interview and documentation.The results of self-empowerment expressed by individuals 'self' entrepreneurial poor who are supported to increase the income and standard of living better. Individual